2012
DOI: 10.1016/j.jvs.2011.10.106
|View full text |Cite
|
Sign up to set email alerts
|

The number of patent tibial vessels does not influence primary patency after nitinol stenting of the femoral and popliteal arteries

Abstract: The number of patent tibial vessels does not influence the primary patency of primarily stented femoral and popliteal arteries. TASC II classification appears to be significantly more predictive of initial failure after angioplasty and stenting of these vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Especially, in the endovascular treatment of the femoropopliteal artery, BTK arteries act as an outflow runoff vessel, and it can affect the outcomes of femoropopliteal intervention itself. 1 -4,6,7,9,13 In addition, the existence of BTK lesions can also reflect a high burden of atherosclerosis and be associated with specific cardiovascular comorbidities and risks. Here, we focused on the clinical implication of poor tibial runoff caused by the existence of BTK lesions on femoropopliteal intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Especially, in the endovascular treatment of the femoropopliteal artery, BTK arteries act as an outflow runoff vessel, and it can affect the outcomes of femoropopliteal intervention itself. 1 -4,6,7,9,13 In addition, the existence of BTK lesions can also reflect a high burden of atherosclerosis and be associated with specific cardiovascular comorbidities and risks. Here, we focused on the clinical implication of poor tibial runoff caused by the existence of BTK lesions on femoropopliteal intervention.…”
Section: Discussionmentioning
confidence: 99%
“…14 -16 The effect of poor distal runoff and the clinical efficacy of concomitant tibial intervention after superficial femoral artery intervention was reported. 1 -4 Black et al reported that insulin-dependent diabetes mellitus, poor runoff into the foot, and renal insufficiency were associated with treatment failure after infrainguinal endoluminal intervention. 17 Davies showed that patency, freedom from recurrent symptoms, and limb salvage were affected by poor runoff vessels after superficial femoral artery endoluminal intervention in patients with critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the number of runoff vessels improves outcomes in patients with infra-inguinal arterial occlusive disease undergoing endovascular angioplasty [ 2 , 8 , 9 ]. In contrast, another study has reported that the number of tibial vessels did not significantly influence the outcomes of 289 limbs in 236 patients with primary endovascular stenting of the femoral and popliteal arteries, as determined at seven years after surgery [ 10 ]. In this study, the number of distal runoff vessels likewise did not have a statistically significant effect.…”
Section: Discussionmentioning
confidence: 99%